Kebaya Fashion Quality 'Veloura Merupa' with the Application of Illusion Bustier - Revalin Trisany; Wahyu Fitriani; Adhi Kusumastuti; Yoela Meidiana (Universitas Negeri Semarang, 2026)
Modern kebaya continues to develop through the application of various fashion design and construction techniques that aim to improve aesthetic value and product quality. One of the techniques that is widely used is the bustier illusion, which is a construction technique that creates a visual illusion on the bustier so that it produces an elegant look and blends in with the wearer's body. This article aims to describe the quality of Veloura Merupa kebaya clothing that applies the illusion bustier technique. The method used is descriptive with a product analysis approach. The aspects analyzed include design quality, fashion construction, material suitability, application of decorative techniques, and the quality of the final appearance of the fashion. The results of the analysis show that the Veloura Merupa kebaya has good quality through the application of an illusion bustier that is able to shape the body silhouette proportionally, the use of materials that support comfort and aesthetics, and application details that give a luxurious and elegant impression. The combination of burgundy colors, transparent lace, draping, and sequin applications strengthens the feminine and classy character of modern kebaya. Thus, the application of the illusion bustier on the Veloura Merupa kebaya is able to improve the visual quality and aesthetic value of the overall fashion.